GMP-conformant on-site manufacturing of a CD133+ stem cell product for cardiovascular regeneration. Issue 1 (December 2017) - Skorska, Anna; Müller, Paula; Gaebel, Ralf; Große, Jana; Lemcke, Heiko; Lux, Cornelia; Bastian, Manuela; Hausburg, Frauke; Zarniko, Nicole; Bubritzki, Sandra; Ruch, Ulrike; Tiedemann, Gudrun; et al.
Abstract Background CD133+ stem cells represent a promising subpopulation for innovative cell-based therapies in cardiovascular regeneration. Several clinical trials have shown remarkable beneficial effects following their intramyocardial transplantation. Yet, the purification of CD133+ stem cells is typically performed in centralized clean room facilities using semi-automatic manufacturing processes based on magnetic cell sorting (MACS®). However, this requires time-consuming and cost-intensive logistics. Methods CD133+ stem cells were purified from patient-derived sternal bone marrow using the recently developed automatic CliniMACS Prodigy® BM-133 System (Prodigy). The entire manufacturing process, as well as the subsequent quality control of the final cell product (CP), were realized on-site and in compliance with EU guidelines for Good Manufacturing Practice. The biological activity of automatically isolated CD133+ cells was evaluated and compared to manually isolated CD133+ cells via functional assays as well as immunofluorescence microscopy. In addition, the regenerative potential of purified stem cells was assessed 3 weeks after transplantation in immunodeficient mice which had been subjected to experimental myocardial infarction. Results We established for the first time an on-site manufacturing procedure for stem CPs intended for the treatment of ischemic heart diseases using an automatized system. On average, 0.88 × 106 viable CD133+ cells with a mean log10 depletion of 3.23 ± 0.19 of non-target cells were isolated. Furthermore, we demonstrated that these automatically isolated cells bear proliferation and differentiation capacities comparable to manually isolated cells in vitro. Moreover, the automatically generated CP shows equal cardiac regeneration potential in vivo. Conclusions Our results indicate that the Prodigy is a powerful system for automatic manufacturing of a CD133+ CP within few hours. Compared to conventional manufacturing processes, future clinical application of this system offers multiple benefits including stable CP quality and on-site purification under reduced clean room requirements. This will allow saving of time, reduced logistics and diminished costs.